Challenging the Dominant Discourse: Khan’s My Guantanamo Diaries and the Rhetoric of the War on Terror - Jeffrey Carr (Intersections, 2020)
This study juxtaposes Mahvish Rukhsana Khan’s powerful memoir My Guantanamo Diary: The Detainees and the Stories They Told Me (2008) with the post-9/11 rhetoric of political leaders and the mainstream media in the United States during the first decade of the twenty-first century. In her work, Khan exposes the extreme, dehumanizing conditions endured by military prison detainees – many of whom Khan argues were falsely arrested – and advocates for their right to receive fair hearings. The several examples of evident torture revealed by the interviewed detainees throughout the text contrast sharply with the rhetoric from speeches and interviews of early twenty-first century American political leaders, such as President George W. Bush and Vice President Dick Cheney, and the news coverage from neoliberal media outlets like CNN and Fox News. Similarly, the brutal representations in Khan’s memoir contrast with the largely positive depictions of torture in popular films and television programs. To support the validity of Khan’s claims, the article will also consider the available War on Terror-era interrogation logs from the Guantanamo Bay military prison camp. This study seeks to illustrate the ability of prevailing power structures to interpellate consumers of mass media while simultaneously suggesting that literature possesses a unique potential to challenge dominant discourses, as it has done throughout history. Finally, this paper argues that works by Khan and other Muslim American authors have the power to disrupt the current racist and xenophobic episteme and challenge the ideological consensus fostered by mainstream media.